Implementasi Integrated Fishfolk Training untuk Peningkatan Kapasitas Pengemasan dan Pemasaran Produk Olahan Udang pada Kelompok Nelayan Pengolah Udang Desa Pidodo Kulonelompok Nelayan Pengolah Udang Desa Pidodo Kulon - Indriyani Indriyani; Hanifa Alsaba Kaneishia; Dea Sandra Isabella; Satsya Yoga Baswara; Rakha Mukti Rahardi (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
Empowering coastal communities by improving packaging and digital marketing skills is an important strategy to strengthen the competitiveness of local products. This community service initiative was carried out using a Participatory Action Research approach in Pidodo Kulon Village, Patebon District, Kendal Regency. The Integrated Fishfolk Training program involved 30 members of the Shrimp Processing Fishermen Group to enhance their technical and socio-economic capacity through hygienic packaging and digital-based marketing training. The activities included socialization, participatory problem identification, joint action planning, hands-on training, and continuous evaluation. The results showed an increase in packaging knowledge from 46.80 to 62.40 and marketing knowledge from 54.00 to 65.60, with 83% of participants applying hygienic and aesthetic packaging standards. Social changes were reflected in greater attention to product quality, the emergence of new local leaders, and rising motivation to expand businesses through digital platforms. Overall, this participatory approach effectively supports sustainable technical and socio-economic improvement.